Perceptions of Competencies Developed in an Active Learning Course Featuring the Design of Web-Based Instruction on Mathematics - Tokmak, Hatice Sancar; Incikabi, Lutfi (IGI Global, 2015)
This chapter presents a research study on mathematics education pre-service teachers' perceptions of competencies developed in an active learning course. During the course, the pre-service teachers designed web-based instruction (WBI) to teach mathematics to a targeted group of children. Data were collected through a demographic questionnaire, unstructured focus group interviews, open-ended questionnaires, and WBI design documents. WBI documents were analyzed according to Khan's (1997) identified components. The results of the study showed that, according to the mathematics education pre-service teachers, their internet search skills, content knowledge about distance education, web interface design skills, and technological knowledge increased or improved due to the WBI project. Moreover, participants observed how the constructivist philosophy did not apply to their designs. In addition, their designs were created from the perspectives of users rather than producers, as many components of WBI were not taken into account during or after the project.
Keywords: 4. Education